Parents’ Communication Strategies in Building Internet Media Literacy for Youth in Muslim Family in Tanjung Mulia Medan Deli - Abdul Karim Batubara; Suwardi Lubis; Syukur Kholil (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The research aims to find out the communication strategies carried out by Muslim family towards youth in accessing the internet, analyzing internet content, evaluating internet content, responding to internet content and finding the results of communication strategies carried out by Muslim family in building internet media literacy for youth in Tanjung Mulia Medan Deli. This research uses field research with a qualitative approach. The informants of this study is one family located in Tanjung Mulia Subdistrict, Medan Deli. Determination of informants using purposive sampling techniques. Research data collection using interviews and observation. While the data analysis technique used is using Spradley Model data analysis. To maintain data validity, data triangulation techniques are used. The results of the study revealed that parents' communication strategies in controlling internet access carried out by their children by providing time limits for their children in accessing the internet. Parents still provide supervision, time restrictions and remind their children to pay attention to internet usage. Communication strategies applied by parents towards analyzing internet content that is often accessed by freeing their children in choosing and accessing internet content and discussing with parents when they find new information and negative content. The strategy taken by parents in evaluating internet content for children is to choose internet content and discuss it with other family members. The communication strategies of parents in responding to internet content carried out by their children is by giving advice on an ongoing basis and giving a warning to their children. It can make their children feel cared for by their parents. As well as to build a Communication Strategies of Media Literacy for Youth in Muslim Family by using Islamic communication approach that is sourced from the Al Qur’an and Hadith.